Validity Assessment of the Persian Version of the Nordic Safety Climate Questionnaire (NOSACQ-50): A Case Study in a Steel Company - Yadolah Yousefi; Mehdi Jahangiri; Alireza Choobineh; Hamidreza Tabatabaei; Sareh Keshavarzi; Ali Shams; Younes Mohammadi (Elsevier, 2016)
Background: The Nordic Safety Climate Questionnaire-50 (NOSACQ-50) was developed by a team of Nordic occupational safety researchers based on safety climate and psychological theories. The aim of this study was to develop and validate the Persian version of NOSACQ-50 and assess the score of safety climate on a group of workers in a steel company in Iran. Methods: The Persian version of NOSACQ-50 was distributed among 661 employees of a steel company in Qazvin Province (Iran). Exploratory factor analysis (EFA) and confirmatory factor analysis were used to determine the dimensions of the questionnaire. The reliability of the questionnaire was assessed using Cronbach α coefficient. Pearson correlation test was applied to investigate the correlation between different dimensions. Results: The results of EFA showed that the Persian version of NOSACQ-50 consisted of six dimensions. The Cronbach α coefficient of the questionnaire was 0.94. The mean score of safety climate in all dimensions was 2.89 (standard deviation 0.60). Conclusion: The Persian version of NOSACQ-50 had a satisfactory validity for measuring safety climate in the studied Iranian population.